Homestay development strategy at Yeh Gangga Beach tourist destination Tabanan-Bali - Ni Nyoman Ardani; Isa Wahjoedi Dwi Poetranto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Yeh Gangga Beach is one of the tourist destinations in Tabanan, which has many attractions at affordable prices. Accommodation in this destination is unique with the traditional design and a lot of environmental activities. The main problems in this accommodation (homestay) are marketing and operation. Many tourists seem unfamiliar with the accommodation, which results in limited market reach. In addition, unstandardized operations have made the performance low and unable to provide maximum tourist satisfaction. This study aims to determine the right strategy for developing homestays and destinations with a local community-based strategy based on tourist characteristics, motivations, and analyzed results. This study used qualitative data collection such as interviews (homestay owners and village officials), observation, questionnaires, and documentation study. By knowing the internal factor (Strength, Weaknesses) and external factors (Opportunity and Threat) of the homestays will be found the strategy to improve the standard of the homestay in Yeh Gangga Beach. Based on observation, questionnaires and interviews with stakeholder and the SWOT analysis indicated as follows: 1). Homestays at Yeh Gangga beach need promotion, this can be done with doing a collaboration with travel bureau who works for a tour package and digital marketing via social media. 2). To obtain a legal license in building homestay, this needs the government involved. 3) In order to meet good administrative or improve management standard requires training or workshop from organizations that are experts in homestay or accommodation administration. 4) Focus Group Discussion (FGD) of homestays owners, village officials, and academics to improve homestays and destination standards. 5) To form a tourism awareness group (POKDARWIS) that will be more responsible for the sustainability of all tourism activities, including homestays as a component of tourism in Yeh Gangga and also beach cleanliness. 6) Create new products with better quality and competitive prices such as special souvenirs to show the characteristic of Yeh Gangga Beach. 7) Community synergy to tackle the waste problem.